Integrating Character Education as a Development Effort Behavior Social Students at MTs Negeri 1 Palu City - Nurjanna; Nuraedah; Misnah (Kirana Publisher (KNPub), 2024)
character building can made shield as well controller , limiter self for participant educate For avoid things negative that violates existing values .​ This matter will more critical happen when parental treatment​ rough or harsh on children them , then form violence or rudeness the practiced by children they in finish problem they daily . Formulation problem How integration education character in how is learning at MTs Negeri 1 Palu City? integration education character outside​ how is learning at MTs Negeri 1 Palu City? effort coaching behavior social participant studied at MTs Negeri 1 Palu City. Research purposes For know effort coaching behavior social participant studied at MTs Negeri 1 Palu City. Research methods This use study qualitative , research qualitative often called method study naturalistic Because his research carried out in natural conditions ( natural setting), also known as method ethnography , because in the beginning method This more Lots used For study field anthropology culture ; called as method qualitative , due to the data collected and its analysis more nature qualitative . Study qualitative addressed For understand phenomenon social perspective participants which are the people invited interviewed , observed , asked provide data, opinions , thoughts , perceptions . Research result integration education characters at MTs Negeri 1 Palu City are in line with middle curriculum​ applied , ie curriculum independent For class VII ( seven ) which requires values education character No only applied in learning but also outside learning .